2020
DOI: 10.1021/acs.jpcb.0c02808
|View full text |Cite|
|
Sign up to set email alerts
|

Energy Conversion and Biocompatibility of Surface Functionalized Magnetite Nanoparticles with Phosphonic Moieties

Abstract: Magnetite nanoparticles (MNPs) were synthesized using two distinctly different approaches, co-precipitation (CP) and thermal decomposition (TD), and further surface functionalized with organophosphonic ligands containing different numbers of phosphonic groups. We have shown that it is possible to fabricate flower-like assemblies of MNPs through TD at lower temperatures, whereas CP MNPs formed agglomerates of particles with broad size distribution and irregular shapes. The effect of the organophosphonic ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…The FTIR−ATR spectra of the ETI reference show typical bands in the most interesting spectral range of 1300−800 cm −1 that is predominantly occupied by vibration modes of different phosphor-containing structural units (O−P−O, P−OH, P− O, P�O, etc.). 29,42 However, the spectra of the bare Fe 3 O 4 MNPs present a characteristic shoulder band with a maximum of around 591 cm −1 that is attributed to the vibrations of the iron cation located at the tetrahedral site. 29 Other very lowintensity peaks are related to the presence of residual organics.…”
Section: Kmentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR−ATR spectra of the ETI reference show typical bands in the most interesting spectral range of 1300−800 cm −1 that is predominantly occupied by vibration modes of different phosphor-containing structural units (O−P−O, P−OH, P− O, P�O, etc.). 29,42 However, the spectra of the bare Fe 3 O 4 MNPs present a characteristic shoulder band with a maximum of around 591 cm −1 that is attributed to the vibrations of the iron cation located at the tetrahedral site. 29 Other very lowintensity peaks are related to the presence of residual organics.…”
Section: Kmentioning
confidence: 99%
“…29,42 However, the spectra of the bare Fe 3 O 4 MNPs present a characteristic shoulder band with a maximum of around 591 cm −1 that is attributed to the vibrations of the iron cation located at the tetrahedral site. 29 Other very lowintensity peaks are related to the presence of residual organics. In the case of star-like, cubic, and tetradodecahedral MNPs, the IR spectra show mutual features.…”
Section: Kmentioning
confidence: 99%
“…Recently, considerable interest has been faced towards exploitation of multimodal heat induction by the use of the simultaneous action of AMF and NIR. 20–25 The trick is to take the advantage out of the two totally independent mechanisms of energy conversion into heat that allow to achieve much faster sample heating and reduce the development of thermotolerance by cells that is characteristic of slow heating rates. 26 It is also possible to go beyond the maximum temperature that can be achieved by using separate mode, to limit the concentration of MNPs if needed, or to reduce the overall exposure time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a post-treatment surface modification after particle synthesis is superior in that the surface polarity can be changed while maintaining their shape and size. Therefore, we focused on a ligand exchange reaction using polar ligands. For this purpose, a carboxyl group (−COOH) is a good candidate for controlling the surface polarity because the surface potential will change after deprotonation treatment. , In addition, introduction of functional groups can not only improve the water dispersibility but can also be used as a binding site for biomolecule conjugation. , On the other hand, there are some monomeric surface modifications for Fe 3 O 4 NPs that utilize various anchoring groups such as −COOH, siloxane (−Si­(OR) 3 ), and phosphonic acid (−PO 3 H 2 ) to help improve the dispersion stability and introduction of functional molecules. , Among these functional molecules, phosphonic acid shows high binding stability to the Fe 3 O 4 surface (the binding energy of Fe–O–P is 530 eV) and acceptable biocompatibility. , Hence, we focused on the surface modification with phosphonic acid by a simple ligand exchange reaction. To date, the ligand exchange reaction has been utilized to introduce functionalized ligands on the surface of Fe 3 O 4 NPs with phosphonic acid. ,, Liang et al reported that the poly­(ethylene glycol) (PEG)-modified Fe 3 O 4 NPs doped with MnO were synthesized by the ligand exchange reaction with phosphonic acid-substituted PEG for magnetic resonance imaging applications .…”
Section: Introductionmentioning
confidence: 99%
“…41,45−47 Among these functional molecules, phosphonic acid shows high binding stability to the Fe 3 O 4 surface (the binding energy of Fe−O−P is 530 eV) 47−49 and acceptable biocompatibility. 50,51 Hence, we focused on the surface modification with phosphonic acid by a simple ligand exchange reaction. To date, the ligand exchange reaction has been utilized to introduce functionalized ligands on the surface of Fe 3 O 4 NPs with phosphonic acid.…”
Section: ■ Introductionmentioning
confidence: 99%